Document Verification And Authentication By Using Password Based Qr Code Signature With Rsa 2048, Aes Encryption, And Sha-256 - Adithia, Mariskha Tri; Elianora, Naomi; Veronica, Maria (Informatika, Universitas Jenderal Soedirman, 2026)
This research presents a secure digital-signature framework for document authentication using QR Codes, combining three modern cryptographic primitives: RSA 2048-bit for digital signing, SHA-256 for document-integrity verification, and password-based AES encryption to protect the signer’s private key. The system addresses a recurring limitation in previous QR-Code-based signature schemes—the absence of secure private-key storage—by deriving AES keys from user passwords and salts, ensuring that RSA private keys are never stored in plaintext. A web-based implementation was developed to support user registration, signature generation, and document verification, requiring only a PDF file and the associated password from users. Functional testing demonstrates that the system accurately authenticates signer identities, detects any modification to document content, identifies incorrect document numbers, and rejects invalid or non-signature QR Codes. These results confirm that the combination of RSA 2048, SHA-256 hashing, and password-derived AES encryption effectively ensures confidentiality of private keys while preserving document integrity and authenticity. The approach also prevents common forgery scenarios, including document substitution, unauthorized content changes, and QR Code misuse.